Description of the first endemic Polistes Latreille, 1802 from Sulawesi (Hymenoptera: Vespidae: Polistinae) - Selis, Marco (Zootaxa, 2018)
A new species of Polistes Latreille, 1802 from Sulawesi, namely Polistes (Polistella) celebensis Selis, sp. nov., is described and figured. This is the first endemic species of this genus from Sulawesi.